Conversion of Undaria pinnatifida residue to glycolic acid with recyclable methylamine in low temperature hydrothermal liquefaction. (March 2017) - Chen, Yongxing; Ren, Xiulian; Wei, Qifeng
Highlights: HTL of biomass with methylamine was reported for the first time. The main composition of aqueous phase was glycolic acid. Highest yield of glycolic acid was 46.52%. The main compositions of bio-oil were saturated and unsaturated fatty acids. The highest recovery rate of methylamine was 99.28%. Abstract: The conversion of Undaria pinnatifida residue to glycolic acid was carried out using methylamine as catalyst by hydrothermal method at relatively low temperature. GC–MS and HPLC were used to identify the composition of bio-oil and liquid products which provide the knowledge of the chemical reaction pathways of the hydrothermal liquefaction. The main liquid product was organic acid which contained glycolic acid, lactic acid, formic acid and acetic acid. And the major organic acid was glycolic acid with the highest yield of 46.52% or 33.98% of dry biomass. Methylamine promoted the dissolution of cellulose from Undaria pinnatifida residue, and significantly improved the yield of glycolic acid. The mechanism of HTL was investigated and the results show that the carbocation C3 was attacked by methylamine molecule which led to the high yield of glycolic acid. In addition, the recovery of methylamine was studied and the highest recovery rate reached 99.28%.